Neurotherapeutic potential of synthetic cannabinoid receptor agonist, WIN55,212-2 on Aluminium chloride and D-galactose- induced cognitive impairments in male Wistar rats - Onesimus, Mahdi (2021)
Cognitive impairments and neurotransmission dysfunction have been linked to old age diseases including Alzheimer’s disease (AD). Aluminium has been reported to act as a neurotoxic metal, whereas D-galactose (D-gal) has been established to be a senescence agent. Donepezil is in a class of medications called cholinesterase inhibitors. It improves mental function such as memory and attention by increasing the amount of a certain naturally occurring substance in the brain. WIN55,212-2 (WIN), is a potent cannabinoid agonist which has been reported to restore neurogenesis in aged-rats in addition to its neuroprotective roles on oligodendrocytes as well as thermoregulation related to the activation of central CB1 receptors. However, there is paucity of information with regards to therapeutic potentials of WIN on Aluminium chloride (AlCl3) and D-gal induced rat model. Hence, the present study established AD-like rat model of neurotoxicity and cognitive impairment induced by AlCl3 and D-gal in order to explore the therapeutic potentials of WIN for the treatment AD-like symptoms in rats. Healthy male albino Wistar rats weighing between 200 g - 250 g were injected with D-gal 60 mg/kg intra peritoneally (i.p), while AlCl3 (200 mg/kg) was orally administered once daily for 10 consecutive weeks. For behavioural assessments: elevated plus maze (EPM), open field test (OFT), Morris water maze (MWM), Novel object recognition (NOR) and T-maze tests were performed. Further, histopathological examinations of the hippocampi and the prefrontal cortices were also carried-out besides, measurements of acetylcholine (ACh) and amyloid beta of the rat’s brains. Subsequently, commencing from week 8 of the experiment, rats were co-administered with WIN (0.5, 1 and 2 mg/kg) and donepezil 1 mg/kg until week 11. Behavioural assessments of the rats and morphological analysis (Nissl’s staining and light microscopy) of their brains were carried out. Further, oxidative stress biomarkers: Malondialdehyde (MDA), superoxide dismutase (SOD) and glutathione (GSH) were assessed. The results revealed that rats treated with AlCl3 200 mg/kg/day and D-gal 60 mg/kg/day showed cognitive impairments in both spatial and non-spatial learning and memory tests, which is also associated with marked neuronal loss (p < 0.05), increased oxidative stress (p < 0.05) and decreased ACh level (p < 0.05) in their brains. Additionally, significant decrease in the expressions of glial fibrillary protein (GFAP) (p < 0.05), Nestin (p < 0.05) and high levels of amyloid beta 42 (Aβ42) in their brains were also evident. However, administration of WIN (0.5 mg/kg/day, 1 mg/kg/day and 2 mg/kg/day) doses reversed the cognitive impairments and the associated AD-like pathologies. As there was increases in the levels of ACh SOD and GSH, while a significant decrease in the levels of MDA and Aβ42 were also observed besides attenuation of aberrant cytoarchitecture of the rat’s hippocampus and prefrontal cortex. Hence, exhibiting therapeutic effects which could be attributed to WIN’s ability to reduce oxidative stress and stop neurodegeneration thereby enhancing cognitive ability. All these findings provide possible scientific evidence to support the exploration of cannabinoid agonist, WIN and other cannabinoids as safe and effective compounds to consider in the treatment of AD related cognitive deficits. Overall, the results of the WIN-treated rats were comparable with the Donepezil group of rats.